Movimentos identitários, educação e povos indígenas: novos desafios para a antropologia da educação - Pádua, Karla Cunha (Cadernos de Estudos Sociais, 2011)
O texto propõe o desafio de pensar os processos de construção de identidades indígenas que se convergem para a área da educação, como acontece no curso de Formação Intercultural de Educadores da FAE- UFMG, como móveis e instáveis – em constante devenir. Busca na Antropologia referências para recusar as identidades como fechadas, fixas e estáveis, utilizando as noções de englobamento e de trilhas, procurando extrair daí algumas implicações para o processo de formação. Palavras-chave: antropologia; movimentos identitários; formação de educadores indígenas. This paper proposes the challenge to reflect on the indigenous identities construction processes related to the educational area, having, as a model, the approach carried out in the Intercultural Formation Course for Indigenous Educators at the Education Department of the Federal University of Minas Gerais (FAE-UFMG), viewing them as movable and unstable processes, and thus in constant change. Based on anthropological references, it is an attempt to refuse such identities as closed, fixed and stable processes. The focus of this paper is to analyze the incorporation of values and goods belonging to the white people into the indigenous culture. Moreover, it studies the pathways which are opened in the forests allowing the Indians connections with the others. In doing so, this study tries to achieve some implications for the formation process of indigenous educators. Key words: Educational Anthropology, identity movements, formation of indigenous educators.